PERSEPSI WISATAWAN TERHADAP KUALITAS DESTINASI PARIWISATA BALI - Hanugerah Kristiono Liestiandre (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2021)
One of the strategic efforts in maintaining customer satisfaction and loyalty can be done by maintaining service quality. Service quality can be defined as the level of guest or consumer satisfaction. The level of guest satisfaction is obtained from the comparison of real services received by visitors, with the previously expected quality values. This research will explore the extent of tourists' perceptions of the quality of Bali destinations. The respondents who will provide information in this study are tourists who meet the requirements as respondents to be able to fill in and provide the information needed when filling out the questionnaire. There were 200 respondents with a composition of 200 domestic tourists and 100 foreign tourists. The analysis technique used in this study was measured using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) methods. The results showed that domestic tourists and foreign tourists have different levels of satisfaction and performance appraisals. As a recommendation, the result of this study could be considered as an evaluation of the quality of tourism destinations in Bali.